ANALISIS HUBUNGAN ANTARA MEDIA SOSIAL DAN KESADARAN MEREK (Studi Kasus pada Komunitas Backpacker Indonesia Wilayah Jabodetabek) - CHAIRANI, PUTTI NURUL; YUNUS, ULANI (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2015)
Research Purpose, to know is there any significant correlation between media social and brand awareness of Logbook application. Research Method, this research was conducted with quantitative methods where research was allowed to use closed questionnaire for data gathering, sample of this research focused on Community of Indonesia Backpacker Jabodetabek Region). The Analysis of this research is using Pearson Correlation to the result of correlation between social media with brand awareness .Result, according to the analysis, social media and brand awareness has significant relations the amount is 65,90%. Conclution, social media has a strong correlation with brand awareness, through this research we expected the social media of Logbook application will be able to build a better relationship with the audience. (PNC)